Conversion of Carbon Dioxide into Solar Fuels Using MgFe2O4 Thermochemical Redox Chemistry - Rahul R. Bhosale (C)
Transforming H2O and CO2 into solar fuels like syngas is crucial for future sustainable transportation fuel production. Therefore, the MgFe2O4/CO2 splitting cycle was thermodynamically scrutinized to estimate its solar-to-fuel energy conversion efficiency in this investigation. The thermodynamic data required to solve the modeling equations were obtained using the HSC Chemistry program. The reduction non-stoichiometry was assumed to be equal to 0.1 for all computations. One of the study’s primary goals was to examine the impact of the inert sweep gas’s molar flow rate on the process parameters related to the MgFe2O4/CDS cycle. Overall, it was understood that the effect of the inert sweep gas’s molar flow rate on the thermal reduction temperature was significant when it increased from 10 to 40 mol/s compared to the rise from 40 to 100 mol/s. The energy needed to reduce MgFe2O4 increased slightly due to the surge in the inert sweep gas’s molar flow rate. In contrast, the energy penalty for heating MgFe2O4-δred from the re-oxidation to thermal reduction temperature significantly decreased. Including gas-to-gas heat exchangers with a gas-to-gas heat recovery effectiveness equal to 0.5 helped reduce the energy demand for heating the inert sweep gas. Overall, although the rise in the inert sweep gas’s molar flow rate from 10 to 100 mol/s caused a drop in the thermal reduction temperature by 180 K, the total solar energy needed to drive the cycle was increased by 85.7 kW. Accordingly, the maximum solar-to-fuel energy conversion efficiency (13.1%) was recorded at an inert sweep gas molar flow rate of 10 mol/s, which decreased by 3.7% when it was increased to 100 mol/s.